2017
DOI: 10.1186/s12888-017-1394-z
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis and examination of the psychometric properties of the eating beliefs questionnaire

Abstract: BackgroundThe Eating Beliefs Questionnaire (EBQ) is a 27-item self-report measure that assesses positive and negative beliefs about binge eating. It has been validated and its factor structure explored in a non-clinical sample. This study tested the psychometric properties of the EBQ in a clinical and a non-clinical sample.MethodA sample of 769 participants (573 participants recruited from the university and general community, 76 seeking treatment for an eating disorder and 120 participating in obesity researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 39 publications
3
27
0
5
Order By: Relevance
“…Overall, the results of this study indicate that the EBQ-18 is a valid, reliable, and clinically useful measure for use in the general population as well as with individuals seeking treatment for binge eating. These findings build upon the previous research that found an earlier, two subscale version of the EBQ to be valid and reliable with clinical and non-clinical samples [ 15 , 16 , 21 ]. These findings are also consistent with the initial examination of the factor structure, internal consistency, and content validity of the current EBQ-18 with a non-clinical sample [ 20 ].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Overall, the results of this study indicate that the EBQ-18 is a valid, reliable, and clinically useful measure for use in the general population as well as with individuals seeking treatment for binge eating. These findings build upon the previous research that found an earlier, two subscale version of the EBQ to be valid and reliable with clinical and non-clinical samples [ 15 , 16 , 21 ]. These findings are also consistent with the initial examination of the factor structure, internal consistency, and content validity of the current EBQ-18 with a non-clinical sample [ 20 ].…”
Section: Discussionsupporting
confidence: 85%
“…In order to develop and evaluate effective psychological treatments for binge eating, it is important to be able to reliably measure the features underlying the development and maintenance of binge eating. Validated measures exist for the measurement of poor self-esteem (e.g., Rosenberg’s Self-Esteem Scale), poor distress tolerance (e.g., Difficulty with Emotional Regulation Scale and Distress Tolerance Scale), as well as the frequency of binge eating itself, restrained eating, the overvaluation of body shape and weight (e.g., Eating Disorders Examination), and others features that are relevant to binge eating [ 15 ]. However, to our knowledge there are only three measures available for the assessment of beliefs about binge eating predicted to maintain binge eating in individuals with eating disorders: the Eating Disorders Thought Questionnaire, Eating Disorders Core Belief Questionnaire, and the Eating Beliefs Questionnaire (EBQ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations